3D-printing of ceramic filaments with ductile metallic cores. (January 2023) - Cai, Qiaosong; Meille, Sylvain; Chevalier, Jérôme; Zhou, Shitong; Bouville, Florian; Tirichenko, Iuliia; Saiz, Eduardo
Graphical abstract: Highlights: Development of a co-extrusion approach for the additive manufacturing of ceramics reinforced by thin (25–100 µm), continuous steel fibres. The technique allows the introduction of thin (10–50 µm) interphases between the fibre and the matrix. The materials exhibit works of fracture up to 1400 J/m 2, two orders of magnitude above the ceramic matrix. Abstract: The additive manufacturing of composite structures can open possibilities in the design and fabrication of devices but also demands new approaches. In this work, we use thermally reversible pastes to fabricate ceramic matrix (Al2 O3 ) composites reinforced with continuous metallic fibres (steel). The approach is based on the micro-extrusion of ceramic–metal filaments with core–shell and layered arrangements. These filaments are employed in the additive manufacturing of dense and light-weight cellular structures that combine the stiffness and strength of the ceramic shell with the fracture resistance and energy absorption capabilities provided by the metal core. The approach can be used to extrude filaments with thin porous interlayers separating the core and the shells to create a weak fibre/matrix interphase. The cellular structures fabricated with these filaments exhibit higher compressive strengths and energy absorption capabilities than those fabricated from pure ceramics. The works of fracture of the dense composites are one to two orders of magnitude above those of the ceramic matrix (10 3 J/m 2 ) while the bending strengths remain comparable to those of 3D printed alumina (200–350 MPa). The technique could be easily extended to other material combinations opening new opportunities in the additive manufacturing of multi-material parts and devices.